Towards a Development Approach to Serious Games - de Freitas, Sara; Jarvis, S. (IGI Global, 2009)
This chapter reviews some of the key research supporting the use of serious games for training in workcontexts. The review indicates why serious games should be used to support training requirements,and in particular identifies “attitudinal change” in training as a key objective for deployment of seriousgames demonstrators. The chapter outlines a development approach for serious games and howit is being evaluated. Demonstrating this, the chapter proposes a game-based learning approach thatintegrates the use of a “four-dimensional framework”, outlines some key games principles, presentstools and techniques for supporting data collection and analysis, and considers a six-stage developmentprocess. The approach is then outlined in relation to a serious game for clinical staff concernedwith infection control in hospitals and ambulances, which is being developed in a current research anddevelopment project. Survey findings from the target user group are presented and the use of tools andtechniques explained in the context of the development process. The chapter proposes areas for futurework and concludes that it is essential to use a specific development approach for supporting consistentgame design, evaluation and efficacy for particular user groups.